Simulation Games Techniques and Lecture Method in Teaching Araling Panlipunan - Castro, Angela Mae S (Asian Journal of Multidisciplinary Studies, 2020)
This study determined the effect of simulation games techniques and lecture method on the academic performance in Araling Panlipunan of Grade 8 students of Eduardo Cojuangco National Vocational High School. It employed experimental research design. In gathering the data, a researcher-made achievement test (pre-test and post-test) was given to the respondents. Frequency, descriptive statistics and analysis of covariance were used to treat the data gathered.Results showed that post-test mean scores shows a strong evidence that there was improvement in the academic performance of students taught in simulation games techniques compared to lecture method. Furthermore, results showed the significant effect of performances of student taught with simulation games technique is better than those taught with lecture method. In addition, results showed that simulation games techniques has significant positive effects on the academic performance of students in Araling Panlipunan. Based on the results, the researcher recommends that the Araling Panlipunan teacher should welcome the use of Simulation games technique in the teaching-learning of Araling Panlipunan in our schools; school administrators should provide contextualized, indigenized and localized games to facilitate meaningful learning in school; school systems must conduct training-workshops, benchmarking summit, institutional building and mentoring to improve and hone the skills of teachers in using and developing games and simulations in the teaching and learning process; furthermore, research is hereby recommended that may look into different variables on the effectiveness of simulation games techniques in teaching Araling Panlipunan.